A Fumonisins Immunosensor Based on Polyanilino-Carbon Nanotubes Doped with Palladium Telluride Quantum Dots - Masikini, Milua; Mailu, Stephen N.; Tsegaye, Abebaw; Njomo, Njagi; Molapo, Kerileng M.; Ikpo, Chinwe O.; Sunday, Christopher E.; Rassie, Candice; Wilson, Lindsay; Baker, Priscilla G. L.; Iwuoha, Emmanuel I. (My University, 2014)
An impedimetric immunosensor for fumonisins was developed based on poly(2,5-dimethoxyaniline)-multi-wall carbon nanotubes doped with palladium telluride quantum dots onto a glassy carbon surface. The composite was assembled by a layer-by-layer method to form a multilayer film of quantum dots (QDs) and poly(2,5-dimethoxyaniline)-multi-wall carbon nanotubes (PDMA-MWCNT). Preparation of the electrochemical immunosensor for fumonisins involved drop-coating of fumonisins antibody onto the composite modified glassy carbon electrode. The electrochemical impedance spectroscopy response of the FB1 immunosensor (GCE/PT-PDMA-MWCNT/anti-Fms-BSA) gave a linear range of 7 to 49 ng L−1 and the corresponding sensitivity and detection limits were 0.0162 kΩ L ng−1 and 0.46 pg L−1, respectively, hence the limit of detection of the GCE/PT-PDMA-MWCNT immunosensor for fumonisins in corn certified material was calculated to be 0.014 and 0.011 ppm for FB1, and FB2 and FB3, respectively. These results are lower than those obtained by ELISA, a provisional maximum tolerable daily intake (PMTDI) for fumonisins (the sum of FB1, FB2, and FB3) established by the Joint FAO/WHO expert committee on food additives and contaminants of 2 μg kg−1 and the maximum level recommended by the U.S. Food and Drug Administration (FDA) for protection of human consumption (2–4 mg L−1). Keywords: anti-fumonisins antibody, impedimetric immunosensor, palladium telluride quantum dots, poly(2,5-dimethoxyaniline)-multi-wall carbon nanotubes, electrochemical impedance spectroscopy
Keywords: Anti-fumonisins; Antibody